ID: 251. Issue 1 (November 2015) - Yoo, Kyung Hyun; Shin, Ha Youn; Oh, Sumin; Hennighausen, Lothar
<x xml:space="preserve">Abstract</x> The sole purpose of the mammary gland is the production of milk and during lactation more than 95% of the mRNA in secreting epithelial cells is contributed by less than 10 genes. Control relays regulating these genes are characterized by two astounding features, their ability to activate expression more than 10, 000-fold during pregnancy and prevent regulatory spillover to neighboring genes. Studies in our laboratory focus on the critical roles of the common cytokine-inducible transcription factor (TF) STAT5 and the chromatin factor CTCF in the establishment of mammary-specific enhancers and the organization of regulatory chromatin domains that prevent regulatory spillover of these powerful enhancers to neighboring genetic loci. Through ChIP-seq experiments we defined the entirety of mammary enhancers in the mouse genome. These enhancers are characterized by the presence of H3K27ac and the joint binding of the TFs STAT5, GR, NFIB and MED1. CRISPR/CAS9 gene editing in mice was used to explore the role of defined STAT5 binding sites in the establishment and function of mammary-specific enhancers. Notably, STAT5 is the pioneer factor in the establishment and function of a subset of mammary enhancers. CTCF ChIP-seq experiments established putative chromatin boundaries of mammary-specific genetic islands. Using CRISPR/CAS9 CTCF sites within and surrounding mammary-specific islands were mutated in mice and their functional significance in establishing mammary-restricted gene regulation was investigated.